Electrochemical properties of nonstoichiometric silicon suboxide anode materials with controlled oxygen concentration. (1st October 2019) - Lee, Jaewoo; Han, Sang A; Lee, Sang-Min; Park, Min-Sik; Kim, Jung Ho
Abstract: Among the silicon (Si)-based anode materials, Si/SiO x is likely to be the best candidate for maintaining structural stability while taking advantage of the high capacity of Si as well as the compatible functionality between Si and SiO x . The oxygen content of SiO x is an especially significant factor for obtaining better performance, because it directly affects electrochemical properties such as reversible capacity, structural stability, and electrical conductivity. Herein, we have synthesized SiO x materials with different oxygen contents via magnesiothermic reduction of silica. The theoretical capacities of a series of Si/SiO x samples were estimated by using X-ray photoelectron spectroscopy, and then those results were compared with empirical results. This work paves the way to predicting the electrochemical performances of lithium-ion battery anodes based on oxygen content in the nonstoichiometric Si/SiO x structure. Graphical abstract: Image 1 Highlights: Si/SiOx materials with various oxygen contents via magnesiothermic reduction of silica had been prepared. The theoretical capacities of a series of Si/SiOx samples had been estimated by using X-ray photoelectron spectroscopy. The optimum oxygen content of Si/SiOx material as a lithium-ion battery anode had been proposed.